Effect of Mn2+ on Upconversion Emission, Thermal Sensing and Optical Heater Behavior of Yb3+ - Er3+ Codoped NaGdF4 Nanophosphors - Qiang, Qinping; Wang, Yuhua (Frontiers in Chemistry, 2019)
In thiswork, we investigate the inﬂuence of Mn2+ on the emission color, thermal sensing and optical heater behavior of NaGdF4: Yb/Er nanophosphors, which the nanoparticles were synthesized by a hydrothermal method using oleic acid as both a stabilizing and a chelating agent. The morphology and crystal size of upconversion nano particles (UCNPs) can be effectively controlled through the addition of Mn2+ dopant contents in NaGdF4: Yb/Er system. Moreover, an enhancement in overall UCL spectra of Mn2+ doped UCNPs for NaGdF4 host compared to the UCNPs is observed, which results from a closed back-energy transfer between Er3+ and Mn2+ ions (4S3/2 (Er3+) → 4T1 (Mn2+) → 4F9/2 (Er3+)). The temperature sensitivity of NaGdF4:Yb3+/Er3+ doping with Mn2+ based on thermally coupled levels (2H11/2 and 4S3/2) of Er3+ is similar to that particles without Mn2+ in the 303 - 548 K range. And the maximum sensitivity is 0.0043 K-1 at 523 K for NaGdF4:Yb3+/Er3+/Mn2+. Interestingly, the NaGdF4:Yb3+/Er3+/Mn2+ shows preferable optical heating behavior, which is reaching a large value of 50 K. These results indicate that inducing of Mn2+ ions in NaGdF4:Yb3+/Er3+ nanophosphors has potential in colorful display, temperature sensor.